Physical Activity in School Recess: Measurements of Physical Activity and the Perspective of School Children from Educational Centers in Urban and Rural Areas - Vargas-Tenorio, Jennifer (2023)
Objective: This study aimed to examine the number of active students and sedentary behaviors, as well as their perceptions of motivation and barriers that prevent the practice of physical activity during recess in rural and urban schools in the province of Heredia, Costa Rica. Methodology: A mixed research study was conducted using the SOPLAY instrument to measure and classify the type of physical activity. In addition, focus groups were held with selected schoolchildren; they were asked about their perception of barriers and motivation to engage in physical activity. The population studied was schoolchildren between 7 and 12 years old enrolled in urban and rural public schools in the province of Heredia. Results: Among the results obtained, statistically significant differences were found. Regarding moderate physical activity (MPA), urban school students were more active than those from rural schools. Concerning vigorous physical activity (VPA), the statistically significant differences were only between the sexes, being greater in boys than in girls. Among the main reasons for the motivation to do physical activity were learning, playing, and socializing. The main barriers the children mentioned were space, the dangers of infrastructure, and violence or bullying. Discussion: It is recommended to invest in improving the infrastructure of schools, disposing of waste materials that put children’s safety at risk so that they can have more room to play, in addition to the acquisition of materials to provide more options and promote the realization of physical activity during recess.